PENGARUH PENGGUNAAN LEMBAR KEGIATAN SISWA (LKS) DILENGKAPI DENGAN PETA KONSEP TERHADAP HASIL BELAJAR BIOLOGI SISWA DI SMAN 1 KOTO BARU KABUPATEN DHARMASRAYA - Yuningsih, Ira; Nurhadi, Nurhadi; Nerita, S.Pd, M.Pd, Siska (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ The background of this research is the studentsâ low grade in biology subject especially in plants material in students at first grade in SMAN 1 Koto Baru Dharmasraya periode 2013/2014. The purpose of this research is to know about the influence of using studentsâ work sheet and map. This research is an experimental research. The population of this research is first grade in SMAN 1 Koto Baru Dharmasraya 2013/2014. The technic which is used by the researcher for taking a sample is purposive sampling. However, the instrument which is used by the researcher is final test of students. Therefore, the result of this research show that the using of studentsâ work sheet and map have an influence to the studentsâ grade. From the research, the researcher get a score from experiment class the score about 78,96 and the standard deviation is 13,97, even though in control class the score about 68,46 and the standard deviation is 10,99 after the researcher do a t test which t count= 3,16 and t table= 1,675 it means that t count > t table. Based on this result, the hypothesis is accepted with the belive periode about 95%. From this research, the researcher conclude that studentsâ work sheet has good impact to the studentsâ result in biology subject at first grade in SMAN 1 Koto Baru Dharmasraya.